Cryptotanshinone reverses the epithelial‐mesenchymal transformation process and attenuates bleomycin‐induced pulmonary fibrosis. (13th April 2020) - Zhang, Qianyu; Gan, Cailing; Liu, Hongyao; Wang, Liqun; Li, Yali; Tan, Zui; You, Jia; Yao, Yuqin; Xie, Yongmei; Yin, Wenya; Ye, Tinghong
Abstract : Idiopathic pulmonary fibrosis (IPF) is a fibrotic interstitial pneumonia that causes pulmonary tissue damage and functional impairment. To investigate the effects of cryptotanshinone on pulmonary fibrosis, the expression of NIH/3T3, HPF, and rat primary pulmonary fibroblasts was measured and found to be inhibited by CPT in a time‐ and concentration‐dependent manner, and the upregulation of α‐SMA expression in NIH/3T3 and HPF cells, which had been stimulated by TGFβ‐1, was decreased after CPT administration. We observed that CPT could reverse the increase in α‐SMA expression and vimentin and the decrease in E‐cad expression in A549 cells, which had been induced by 5 ng/mL TGFβ‐1, indicating that CPT has inhibitory effects in the EMT process. A BLM‐induced pulmonary fibrosis model was established in C57BL/6 mice. The lung coefficient and hydroxyproline content increased significantly in the BLM‐induced group and were decreased in the CPT‐treated group. The expression levels of collagen‐I and α‐SMA and the phosphorylation level of Stat3 were significantly increased, and CPT treatment decreased these levels. Furthermore, the results from the flow cytometry analysis indicated that, in lung tissues, the frequencies of MDSCs, macrophages, DCs and T cells were considerably increased in the BLM‐induced group, while CPT treatment reduced these immunocyte populations.